Financing inclusive education in Iceland - Óskarsdóttir, Edda; Hreinsdóttir, Anna Magnea (Tímarit um uppeldi og menntun, 2023)
Inclusive education is a priority in European and international educational policy. It is based on ideas originating in the human rights movements, the United Nations Convention on the Rights of the Child (no. 19/2013) and the United Nations Convention on the Rights of Persons with Disabilities (2016). Understanding the concept of inclusive education has thus shifted from a focus on general schooling for students with defined special needs or disabilities to developing education that can meet the needs of a diverse group of students (Florian et al., 2017). Implementing school policy depends on those who work in the schools. Therefore, it is vital that a common understanding of the policy is at hand and the necessary knowledge and resources provided to teachers and other staff (Salamon, 2002).European Agency for Inclusive Education and Special Needs carried out an audit of the system of inclusive education in Iceland in 2016 (European Agency, 2017). In its findings, three closely related priorities, or levers, are set out that are considered urgent to implement as soon as possible to ensure the success of the education system. The first is about reaching a common understanding of inclusive education and how to organize it. The second is the importance of reaching an agreement on minimum standards for the provision of services that support education for all in all schools. The third priority, which is the focus of this paper, is the need to undertake a review of the current policies of financing education in the spirit of inclusion and increased efficiency of the school system.There are many indications that the medical view and emphasis on diagnoses are behind a certain part of funding for schools in Iceland, and in the findings of the European Agency's audit (2017) this arrangement is criticized, as it is considered weakness-oriented. This means that it is common to look for deviations or weaknesses in students, instead of thinking about promoting holistic measures within the school and appropriate support that ...